2012
DOI: 10.5897/ajar11.106
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of post harvest technologies used by small-holder farmers in Swaziland

Abstract: Post-harvest technology forms an important component of any agricultural system. It is vital in all circumstances, whether there is surplus or deficit. A lot has been done on the dissemination of postharvest loss reduction technologies in Swaziland, but very little has been done to evaluate the adoption of such technologies. This study evaluated the adoption of post-harvest technologies by smallholder farmers. The objectives were to describe the existing post-harvest technologies in Swaziland and identify fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The efficacy of hermetic storage options has received significant research attention recently in Africa, with a particular focus on hermetic bags and metal silos (Murdock et al, 2012;Baoua et al, 2013;de Groote et al, 2013;Guenha et al, 2014;Singano et al, 2019;Baributsa et al, 2020), as well as the socio-economic aspects (Atibioke et al 2012;Bokusheva et al 2012;Villane et al 2012;Gbénou-Sissinto et al 2018). However, most studies to-date have evaluated up to two different brands of the bags on just one variety of the focal crop or a mixture of varieties, whereas our study compared five brands of hermetic bags, with each brand being compared for three different maize varieties, under two contrasting agro-ecologies and for two consecutive 8 month long storage seasons.…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of hermetic storage options has received significant research attention recently in Africa, with a particular focus on hermetic bags and metal silos (Murdock et al, 2012;Baoua et al, 2013;de Groote et al, 2013;Guenha et al, 2014;Singano et al, 2019;Baributsa et al, 2020), as well as the socio-economic aspects (Atibioke et al 2012;Bokusheva et al 2012;Villane et al 2012;Gbénou-Sissinto et al 2018). However, most studies to-date have evaluated up to two different brands of the bags on just one variety of the focal crop or a mixture of varieties, whereas our study compared five brands of hermetic bags, with each brand being compared for three different maize varieties, under two contrasting agro-ecologies and for two consecutive 8 month long storage seasons.…”
Section: Introductionmentioning
confidence: 99%
“…The sex of the household head had no association with the type of grain storage protectant practice used in the current study. However, in Nigeria, male-headed households were more receptive to postharvest technology adoption than female-headed (Atibioke et al, 2012) while in Swaziland, women were found to be more likely to have adopted postharvest technologies than men (Villane et al, 2012). These examples highlight how culture, gender and geographical location, among other factors, interact and influence the use of grain storage technologies.…”
Section: Factors Associated With the Use Of Different Maize Grain Sto...mentioning
confidence: 99%
“…While significant effort has gone into the development and dissemination of PHL reduction technologies, high losses continue to be recorded in SSA, prompting the need to review factors affecting the adoption and use of postharvest technologies (Mvumi and Stathers, 2003;Atibioke et al, 2012;Bokusheva et al, 2012;Villane et al, 2012;Gbénou-Sissinto et al, 2018).…”
Section: Introductionmentioning
confidence: 99%